Identification of a gut microbiota member that ameliorates DSS-induced colitis in intestinal barrier enhanced Dusp6-deficient mice - Chang, Cherng-Shyang; Liao, Yi-Chu; Huang, Chih-Ting; Lin, Chiao-Mei; Cheung, Chantal Hoi Yin; Ruan, Jhen-Wei; Yu, Wen-Hsuan; Tsai, Yi-Ting; Lin, I-Jung; Huang, Chien-Hsun; Liou, Jong-Shian; Chou, Ya-Hsien; et al. (Cell reports (Cambridge), 2021)
Strengthening the gut epithelial barrier is a potential strategy for management of gut microbiota-associated illnesses. Here, we demonstrate that dual-specificity phosphatase 6 (Dusp6) knockout enhances baseline colon barrier integrity and ameliorates dextran sulfate sodium (DSS)-induced colonic injury. DUSP6 mutation in Caco-2 cells enhances the epithelial feature and increases mitochondrial oxygen consumption, accompanied by altered glucose metabolism and decreased glycolysis. We find that Dusp6-knockout mice are more resistant to DSS-induced dysbiosis, and the cohousing and fecal microbiota transplantation experiments show that the gut/fecal microbiota derived from Dusp6-knockout mice also confers protection against colitis. Further culturomics and mono-colonialization experiments show that one gut microbiota member in the genus Duncaniella confers host protection from DSS-induced injury. We identify Dusp6 deficiency as beneficial for shaping the gut microbiota eubiosis necessary to protect against gut barrier-related diseases. [Display omitted] •Dusp6 deficiency protects against DSS-induced colitis in mice•Dusp6 knockout induces tight junction- and microvilli-associated gene expression•Dusp6 knockout results in elevation of mitochondrial oxygen consumption•A potential anti-colitis bacterium, NHRI-C1-K-H-1-87, is found in Dusp6-knockout mice Chang et al. report that Dusp6 deficiency strengthens the junctions and extends the microvilli, thereby enhancing colonic barrier integrity. Dusp6 deficiency also promotes glucose-to-lipid metabolic switch and elevates mitochondrial oxygen consumption, thereby maintaining the anaerobic state for preserving obligatory bacteria. An anti-colitis anaerobe, NHRI-C1-K-H-1-87, is identified in Dusp6-knockout mice.